Prediction of temperature distributions in peaked, leveled and inverted cone grain mass configurations during aeration of corn - Lawrence, J.; Maier, Dirk E. (My University, 2012)
Three-dimensional heat and momentum transfer for the peaked, leveled, and inverted cone grain mass configurations in a corn silo was studied with aeration airflow rate ranged from 0.26 to 0.31 m³/min-t (0.24 to 0.28 cfm/bu) using the 3D finite element stored grain ecosystem model. Non-uniform airflow models for peaked, leveled, and inverted cone grain mass configurations were developed using the finite volume method. Airflow resistance due to porous media of grain material was implemented using Ergun’s equation and a linear porosity variation with low porosity at the center and maximum at the side. The velocity profile and heat transfer during aeration were quantified for the peaked, leveled and inverted cone grain mass configurations. The change in grain temperature in the inverted cone grain mass configuration was the fastest followed by the leveled and peaked configurations. It took 102, 114, and 186 h, respectively, for cored, leveled, and peaked grain mass configurations to cool the grain from 40°C to below 20°C. For the peaked cone volume, the model predicted an 84-h delay in the cooling front movement (or about 55%) compared to the inverted cone configuration. This has significant implications with respect to fan run time hours, electricity consumption, and the potential for grain spoilage.
Keywords: Non-uniform airflow; Aeration; Peaked; Leveled; Cored; Grain mass configurations; Finite volume method; Finite element method